Development and evaluate an unreliable asynchronous failure detector based on gossip using the CORE (COmmon Research Emulator) (Research, Society and Development, 2021)
A Mobile Ad Hoc NETwork (MANET) is a network of mobile nodes and easy-to-maintain topology and high-strength where users can access a basic communication infrastructure anytime and anywhere without the need for base stations. Failure detectors are "oracles" that, from messages exchanged between nodes, are able to identify faulty nodes. Because detectors can make mistakes, their suspicions are only used to prevent algorithms from waiting indeterminately by a failed node response. Gossip is an epidemic-based algorithm builds on the social phenomenon called gossip, where a node announces (by broadcast or multicast) information to its local neighbors (within its transmission range) information about a group of neighboring (local or remote) nodes. This paper presents an implement and evaluate an unreliable asynchronous failure detector based on gossip using the CORE (COmmon Research Emulator).